Saving and Growth in Egypt - Hevia, Constantino; Loayza, Norman (2012)
This study illustrates the mechanisms linking national saving and economic growth, with the purpose of understanding the possibilities and limits of a saving-based growth agenda in the context of the Egyptian economy. This is done through a simple theoretical model, calibrated to fit the Egyptian economy, and simulated to explore different potential scenarios. The main conclusion is that if the Egyptian economy does not experience progress in productivity -- stemming from technological innovation, improved public management, and private-sector reforms -- then a high rate of economic growth is not feasible at current rates of national saving and would require a saving effort that is highly unrealistic. For instance, financing a constant 4 percent growth rate of gross domestic product per capita with no improvement in total factor productivity would require a national saving rate of around 50 percent in the first decade and 80 percent in 25 years. However, if productivity rises, sustaining and improving high rates of economic growth becomes viable. Following the previous example, a 2 percent growth rate of total factor productivity would allow a 4 percent growth rate of gross domestic product per capita with national saving rate in the realistic range of 20-25 percent of gross domestic product.